Since each term is -3/4 times the previous term we know that this is a geometric sequence with a common ratio of -3/4. Any geometric sequence can be expressed as:
a(n)=ar^(n-1), a=initial term, r=common ratio, n=term number
Since we do know the common ratio is -3/4 and that a(3)=9/16 we can find the value of a, the initial term.
9/16=a(-3/4)^2
9/16=9a/16
1=a, so the initial term is 1 so now we have the formula for our geometric sequence.
a(n)=1*(-3/4)^(n-1)
a(n)=(-3/4)^(n-1) so the 7th term is:
a(7)=(-3/4)^6
a(7)=729/4096